PENGARUH E-SERVICE QUALITY DAN PERCEIVED VALUE TERHADAP LOYALITAS PELANGGAN MARKETPLACE (STUDI KASUS PELANGGAN TOKOPEDIA) - Rory Handriano; Mohdari - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract, This research aims to analyze the significant and simultaneous influence of E-service Quality & Perceived Value on Marketplace customer loyalty. The method used is a qualitative analytical method, in which the instrument or measuring instrument in this research is a questionnaire or questionnaire containing granules of questions to be responded by research respondents using a Likert scale. This research, it was found that the transaction and customer loyalty is not yet optimal at one of the Marketplace companies in Indonesia, especially in the city of Banjarmasin (in this case Tokopedia), which can be seen from the relatively fixed transaction data from 2017 to 2019 due to low customer loyalty. One effort that can be done so that transactions and customer loyalty can be improved is by improving the quality of E-Service Quality, especially in the dimensions that have the lowest value, namely delivery, so that the way of delivering information to customers and improvement of the Perceived Value variable in the quality functional value categories such as quality features more complete can be further improved.